Developing methodology to evaluate eye lens dose for medical staff: preliminary results - Tran , Yen Nhi; Pham, Nhu Tuyen; Dang, Thanh Luong (Nuclear Science and Technology, 2026)
Due to epidemiological evidence on the increasing incidence of cataracts in interventional cardiologists, the ICRP has recommended reducing the eye lens dose limit from 150 mSv/year to 20 mSv/year. Thus, the current status of occupational dose assessment for healthcare workers shows that it requires more precise measurements of eye lens dose. We investigated dosimetric characteristics of OSLD nanoDot and InLight type by using a multi–filter technique to determine the average air kerma of the incident beam and other essential dosimetric factors such as the relative energy responses and conversion coefficients from the air kerma to personal dose equivalent operational quantities Hp(d). Based on assessing and analyzing factors that influence Hp(d), the methodologies were developed to evaluate eye lens dose for medical staff, especially high-risk subjects such as interventional physicians. The results show that 3 methods to evaluate eye lens dose have been deployed in the cardiovascular intervention department: directly by nanoDot dosimeter, indirectly by personal dosimeter (InLight), and quick method based on the relationship with exposure duration. It was found that one interventional cardiologist exceeded the dose limit of 20 mSv/year for eye lens dose without protective measures. In other words, the risk of cataracts is possible when the cumulative dose for 30 working years is considered